2013
DOI: 10.1016/j.meegid.2013.06.024
|View full text |Cite
|
Sign up to set email alerts
|

Clonal complexes 104, 109 and 113 playing a major role in the dissemination of OXA-carbapenemase-producing Acinetobacter baumannii in Southeast Brazil

Abstract: Carbapenem resistance among Acinetobacter baumannii strains isolated from clinical settings in Brazil has increased dramatically in the last 10 years due to the emergence and dissemination of OXA-type carbapenemase encoding genes. This study aimed to characterize the presence of carbapenem-hydrolyzing class D β-lactamases (CHDL)-encoding genes and clonal complexes playing a major role in the dissemination of OXA-carbapenemase-producing A. baumannii in Southeast Brazil. A total of 74 A. baumannii strains isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 37 publications
0
32
1
3
Order By: Relevance
“…It may be that a more recent transfer onto plasmids by this enzyme group has limited its spread to date. In contrast, the bla OXA-143-like enzymes, which are closely related to the bla OXA-40-like enzymes, have been identified only in Brazil (58,61,125). However, this apparent discrepancy may be explained by the close cultural connections between South America, Portugal, and Spain.…”
Section: Geographical Disseminationmentioning
confidence: 99%
See 1 more Smart Citation
“…It may be that a more recent transfer onto plasmids by this enzyme group has limited its spread to date. In contrast, the bla OXA-143-like enzymes, which are closely related to the bla OXA-40-like enzymes, have been identified only in Brazil (58,61,125). However, this apparent discrepancy may be explained by the close cultural connections between South America, Portugal, and Spain.…”
Section: Geographical Disseminationmentioning
confidence: 99%
“…Subsequent studies have identified isolates carrying bla OXA-23-like genes from all over the world (40,(119)(120)(121)(122)(123). Of all of the acquired OXA-type ␤-lactamases, those of the bla OXA-23-like group currently appear to be the most widespread and are particularly prevalent in Africa (123), South America (120,124,125), and East and Southeast Asia (53,126). While not as prevalent as the bla OXA-23-like genes, the bla OXA-58-like genes are also globally distributed (53,(126)(127)(128)(129).…”
Section: Geographical Disseminationmentioning
confidence: 99%
“…ST2 (clade B) is part of the IC-II lineage, which is widely prevalent throughout Europe and the United States and is frequently implicated in nosocomial outbreaks (20,74,75). ST406 (clade C) was first reported in an epidemiological study of CRAB clinical isolates from Japan (87) and was subsequently identified in Brazil (88). It is closely related to IC-I strains, which are globally disseminated.…”
Section: Figmentioning
confidence: 99%
“…Until now, this ST was not commonly recovered. Indeed, some A. baumannii isolates belonging to ST113 have been identified in Kuwait in 2013, containing plasmids harboring the bla GES-11 carbapenemase gene alone or coharboring the bla OXA-23 gene (10 (11), emphasizing that the dissemination of this carbapenemase gene is not related to a single clone.…”
mentioning
confidence: 99%
“…CRABs have become increasingly isolated in Brazil, with those carrying bla OXA-23 -like and bla OXA-143 -like genes being most prevalent (11). As opposed to what occurs in the rest of the world, with the predominance of ST92/OXA-23 A. baumannii isolates, it seems that CRABs carrying bla OXA-23 -like and bla OXA-143 -like genes mainly belong to multiple STs and clonal complexes CC104, CC109, and CC113 in Latin American countries.…”
mentioning
confidence: 99%